Citizen science through schools: the importance of interpersonal relationships - Ilídio André Costa; Carla Morais; Mário João Monteiro (Cuadernos.info)
The CoAstro: @n Astronomy Condo citizen science project engages, in a mediated process, teachers, astronomers, and science communicators in research and science communication/science education practices. In CoAstro, scientific research objectives were aligned with science communication/science education objectives to engage public with low astronomy awareness. One of CoAstro ´s goals was to understand the effects of the relationships established among the participants, because these are key aspects for engagement. We conducted a case study following the participants during an academic year and collected data through interviews and participant observations. A focus group meeting followed those data collection techniques. The results show the personal benefits of established relationships, institutional effects, changes in the perceived identity roles, and the ability to understand and engage in astronomy research and astronomy communication/education. Understanding social interactions contributes to increase the scope of citizen science projects' and demonstrates its relevance to engaging scientists, science communicators, and school communities, pointing to a path for community empowerment and engagement with science; i.e., a path to unveil a citizen science that moves from mere citizenship to personal comprehensive development: attitudes but also, knowledge.